Low temperature ductility of BA-VAc olefin polymer modified asphalt binders. (10th April 2023) - Wang, Wei; Li, Xinsheng; Shen, Junan; Yuan, Fugen
Highlights: A new asphalt modifier was prepared by free radical polymerization using butyl acrylate (BA) as soft monomer and vinyl acetate (VAc) as hard monomer. BA-VAc polymer can greatly improve the low temperature ductility of asphalt binders at a suitable dose, while the high temperature performance of the modified asphalt is negligibly reduced. BA-VAc polymer reduced the roughness and DMT modulus of asphalt binders, consequently, reduced the overall stiffness of asphalt. Abstract: Low temperature cracking is one of the main failures of asphalt pavements, specifically in cold areas. The ductility of asphalt binders at low temperature is one of the property indexes that are used to characterize cracking resistance of asphalt binders at low temperature. In order to improve the low temperature ductility of asphalt binders, butyl acrylate (BA) as soft monomer and vinyl acetate (VAc) as hard monomer were used for free radical polymerization, and the BA-VAc polymer was then used as a modifier to modify asphalt binders. The modification scheme was optimized by orthogonal test. The modified asphalt binders were mainly evaluated by ductility test and selected other properties. Atomic force microscopy (AFM) was used to investigate the nano-scaled morphology of modified asphalt binders. The results showed that 1) BA-VAc polymer could greatly improve the ductility of asphalt binders, highly depending on the type of base asphalts for their efficient. 2) The high temperature property of asphalt binder slightly decreased, but the compatibility and storage stability of the modified binders became poorly with the dose of BA-VAc polymer got larger and exceeded 6 %. 3) Ba-VAc polymer reduced the volume and number of "bee-like structures" in the 2D morphgraphic results, and also decreased the surface roughness and stiffness of modified binders. 4) The best performance of modified binders was observed for the modification scheme of a 6 % BA-VAc polymer and BA/VAc being a ratio of 6:4 which is produced at a shear temperature of 130 °C, a shear time of 5 min and a shear rate of 1000 r/min.